2010
DOI: 10.1177/112067211002000419
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Retinal Vigabatrin Toxicity in Patients with Partial Symptomatic or Cryptogenic Epilepsy

Abstract: RNFLT measurement with OCT can efficiently identify vigabatrin toxicity in patients with partial symptomatic and cryptogenic epilepsy. Perimetry, contrast sensitivity, and color discrimination assessment might be inconclusive in these particular subgroups of epileptic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…This was recognized by nasal quadrant attenuation and normal temporal thickness with or without inferior and superior changes. The finding of normal thickness of the temporal quadrant in all patients agrees with the results of our study as well as others (Durnian & Clearkin 2008; Akcakaya et al. 2010; Moseng et al.…”
Section: Discussionsupporting
confidence: 94%
“…This was recognized by nasal quadrant attenuation and normal temporal thickness with or without inferior and superior changes. The finding of normal thickness of the temporal quadrant in all patients agrees with the results of our study as well as others (Durnian & Clearkin 2008; Akcakaya et al. 2010; Moseng et al.…”
Section: Discussionsupporting
confidence: 94%
“…1). This technique has also been used in TSC to evaluate the optic nerve thickness of patients treated with vigabatrin, an antiepileptic drug known to cause a GABAergic retinopathy and visual field defect [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that in vigabatrin toxicity, peripapillary RNFL thinning occurs first in the nasal quadrant with sparing of the temporal retina with or without involvement of the superior and inferior retina. 126128 Peripapillary nasal RNFL thinning can be one of the earliest signs of toxicity even before VF loss and has been seen in patients receiving cumulative doses of 1000 g or less in the presence of normal VFs. 129 The time to occurrence of an attenuated RNFL thickness resulting from vigabatrin therapy is unknown, neither is the extent of any further attenuation over time.…”
Section: Review Of Diseasesmentioning
confidence: 99%